Self expression and authenticity in Mohan Hazian’s personal communication through the book “Goresan Seorang Berandal” - Maskuri, M. Ibnu Naufal (Priviet Social Sciences Journal, 2026)
This study looks at how Mohan Hazian shows himself and stays true to who he is through his book "Goresan Seorang Berandal." Mohan, a well-known figure in the creative world, shares his real thoughts and feelings in his writing. His book is not just a recounting of his life story; it is also a way for him to talk about himself and how he deals with the pressures of fame and the expectations of public life. This study uses a descriptive and qualitative approach, focusing on how stories are told. The data were obtained by examining the text, the way words are used, and the symbols that show how Mohan communicates about himself. The findings show that Mohan expresses himself through honest and emotional storytelling, demonstrating bravery in being open and real. His work shows the importance of being true to oneself by rejecting fake ideas and promoting free thinking in urban life. The book acts as a personal space for honest emotions and deep thinking and also stands up against the image-driven culture of the digital world.